Characterizing stem students’ engagement in model-making through the lens of Epistemologies in Practice (EIP) - Pingol, Shermaine Baylon (Animo Repository, 2023)
One of the crucial roles of science education is to provide an authentic learning experience that enables the learners to build an understanding of how the world works as they are being engaged in it. The authentic learning experiences can only be achieved through learner-centered approaches that let them explore and build knowledge constructs on their own. As multiple studies revealed, conventional teaching approaches fail to provide these authentic learning experience due to the limitations brought about by their nature of it. Current science education reforms promote the introduction of science practices in classrooms to shift from learning science as accumulated knowledge to doing science, i.e., engaging in authentic disciplinary work. Driven by this reform goal, this study aimed to determine how Filipino STEM students approach sensemaking during classroom model-making activities. The Epistemologies in Practice (EIP) framework was used as the analytical tool for this study as it aids in surfacing students’ knowledge construction within a collaborative space. To understand the context in which such student engagement occurs, classroom ethnography was employed, drawing on various data sources such as audio/video recordings of classroom sessions, student interviews, field notes, and students’ outputs. Inductive and deductive content analysis were utilized to address the identified research questions. We employed the help of an independent co-coder who completed the analysis independently. The findings revealed that grade 12 STEM students approach the practice of sensemaking in the context of making models by (1) recollecting different resources available to them. (2) asking guidance through their peer and teacher (3) searching for information on their own, and (4) using logic and prior knowledge. In terms of students’ epistemic considerations, it is revealed that students’ epistemic considerations in their knowledge construction starting from most to least were the nature of the knowledge product, audience of the knowledge product, justification of the knowledge product, and generality of the knowledge product. Unexpected results such as the intersection of approaches and epistemology seen in students using logic and prior knowledge and generality of the knowledge constructs and students’ resolution of their cognitive dissonance by practicing critical evaluation of their shared ideas and searching for information on their own were highlighted in this study. The practice of searching information on their own was also identified as one of the emerging themes for students’ approaches in sensemaking. These findings have significant implications for science educators and researchers to support students’ sensemaking and critical thinking through the promotion of science practices as an alternative approach to conventional teaching strategies. Through this study, science educators and researchers will be able to gain a deeper understanding of the students’ epistemic considerations in knowledge construction that will help them to design pedagogical approaches sensitive to students’ needs and interests. Keywords: Science practice, STEM, Model Making, Sensemaking, Classroom ethnography, Epistemologies in practice, Multimodal Interaction analysis